ANALYSIS OF THE CAUSES OF CLAIM REJECTIONS BY MANDIRI INHEALTH INSURANCE COMPANY - Rehulina Br Purba, Farida; Lestari Ramadhani Nasution, Sri; Girsang, Ermi (Pena Cendekia Insani, 2025)
Claim rejection by insurance companies often occurs and in practice not all claims submitted by customers can be accepted. Facts at the research location, namely the Mandiri In health Insurance Company, claim rejection data for the period January-December 2023, namely individual Indemnity 47,730 cases and Managed Care 5,525 cases. The purpose of the study was to analyze the causes of customer claim rejection by the Mandiri In health Medan Insurance Company. Types of qualitative research with methods descriptive. The research informants were determined by purposive sampling consisting of 1 key informant and 5 main informants. The results of the study showed that the procedure for submitting insurance claims at the Mandiri In health Insurance Company in Medan City is by filling out the claim submission form, submitting the original valid and stamped receipt, including the account number, completing all claim document files and submitting them to the company. The causes of claim rejection are incomplete claim files, policy exceptions, ceiling benefit limits, claim expiration, double claim submissions, indications of fraud and administration. The conclusion of the research results is that the cause of the rejection of customer claims by the Mandiri In health Insurance Company came from the customer's error in not being able to fulfill the requirements needed for their insurance claim to be accepted It is recommended that the insurance company management provide training to officers to improve skills in dealing with and explaining problems that cause customer claims to be rejected and increase socialization of insurance products to the public or prospective customers.